“It takes two to tango”: libraries achieving sustainable development goals through preservation of indigenous knowledge on textile craft making (adire) among women (2018)
Indigenous Knowledge (IK) serves as a basic input to sustainable development, perhaps due to its distinctive nature in the knowledge economy. Despite the several benefits of IK to sustainable development, many African nations have lost their cultural and customary knowledge due to inadequate attention of heritage institutions especially libraries, in ensuring that IK constitutes part of their collections. Women are at the forefront of using IK to improve livelihoods in areas such as birth control, food preservation and cultural practices; healthcare and in craft making. However, there is paucity of research on indigenous knowledge preservation on art and craft among women in Nigeria. Using the pragmatic approach embedded within a case study research, the study examined how libraries can partner with indigenous communities on indigenous knowledge preservation. The population of the study comprised librarians, who are heads of libraries in public, academic and national libraries, and women artisans in tie and dye (Adire) making in Abeokuta, Ogun Stater Nigeria. Semi structured interview method was used as data collection techniques. Through the use of purposive sampling technique, ten librarians were' selected while random sampling technique was used to select fifteen women who were considered key informants for the study. Data were analysed using thematic content analysis. The results revealed that indigenous knowledge on adire textiles is not being systematically preserved, but rather retained in family and trade groups. Appropriate recommendations were made based on findings.